Electroacupuncture Attenuates Post-Inflammatory IBS-Associated Visceral and Somatic Hypersensitivity and Correlates With the Regulatory Mechanism of Epac1–Piezo2 Axis - Guo, Jing; Chen, Lu; Wang, Yu-hang; Song, Ya-fang; Zhao, Zhan-hao; Zhao, Ting-ting; Lin, Zhi-ying; Gu, Dong-mei; Liu, Yun-qi; Peng, Yong-jun; Pei, Li-xia; Sun, Jian-hua (Frontiers in Endocrinology, 2022)
Electroacupuncture (EA) is considered to have a therapeutic effect in the relief of irritable bowel syndrome (IBS)-associated visceral hypersensitivity via the reduction of the level of 5‐hydroxytryptamine (5‐HT) and 5-HT3 receptors (5-HT3R). However, whether Epac1/Piezo2, as the upstream of 5-HT, is involved in this process remains unclear. We investigated whether EA at the ST36 and ST37 acupoints alleviated visceral and somatic hypersensitivity in a post-inflammatory IBS (PI-IBS) model mice via the Epac1-Piezo2 axis. In this study, we used 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced PI-IBS as a mouse model. Visceral sensitivity was assessed by the abdominal withdrawal reflex test. Somatic sensitivity was evaluated by the hind paw withdrawal threshold. Quantitative real-time PCR, immunofluorescence staining, ELISA, and Western blotting were performed to examine the expressions of Epac1, Piezo2, 5-HT, and 5-HT3R from the mouse distal colon/L5–S2 dorsal root ganglia (DRG). Our results showed that EA improved the increased visceral sensation and peripheral mechanical hyperalgesia in PI-IBS model mice, and the effects of EA were superior to the sham EA. EA significantly decreased the protein and mRNA levels of Epac1 and Piezo2, and reduced 5-HT and 5-HT3R expressions in the distal colon. Inhibition of colonic Piezo2 eliminated the effect of EA on somatic hypersensitivity. Combined inhibition of colonic Epac1 and Piezo2 synergized with EA in relieving visceral hypersensitivity and blocked the effect of EA on somatic hypersensitivity. Additionally, protein levels of Epac1 and Piezo2 were also found to be decreased in the L5–S2 DRGs after EA treatment. Taken together, our study suggested that EA at ST36 and ST37 can alleviate visceral and somatic hypersensitivity in PI-IBS model mice, which is closely related to the regulation of the Epac1–Piezo2 axis.